Evaluating the multi-dose intramuscular administration of Methotrexate in the early stage of interstitial ectopic pregnancy - Dao, Le Thi Anh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: Interstitial ectopic pregnancy (IEP) occurs when implantation happens in the interstitial part of the fallopian tubes, accounting for 3% of all ectopic pregnancies. This condition poses challenges for surgical intervention due to the difficulty in locating the gestational mass. This study aims to assess the efficacy of multi-dose intramuscular injection of methotrexate (MTX) in treating IEP in the early stages. Methods: A cross-sectional study was conducted at Hanoi Obstetrics and Gynaecology Hospital from January 2018 to July 2019. Patients were treated with intramuscular MTX injections at a dosage of 1 mg/kg/24 hours on the first day, with subsequent doses adjusted based on βhCG concentration. A total of four MTX injections were administered. Results: Among 26 eligible patients, the successful treatment rate was 84.62%. βhCG levels significantly decreased after the third injection. Conclusion: Multi-dose intramuscular MTX injection is an effective and safe treatment option for interstitial ectopic pregnancies in the early stages.